Bank portfolio exposure to emerging markets and its effects on bank market value - Fissel, Gary S.; Goldberg, Lawrence; Hanweck, Gerald A. (Journal of Banking & Finance, 2006)
This study estimates a model of banking company equity returns taking into consideration book value and market value measures of their exposure to emerging markets debt. In this estimation, general systematic market factors, such as the rate of return on the S&P500 stock index and yields on a constant maturity 5-year Treasury note, are held constant such that the exposure variables are accounting for effects due to banks’ exposure to emerging market debt. The results, although not uniform among banking companies, support the hypothesis that the extent of exposure to emerging market debt are factored into the valuation of banking company equity contemporaneously. The inclusion of a market value indicator adds to the explanation of equity returns of some banks. It is also clear that knowing the extent of the exposure on a book value basis is important information alone that may allow investors to take account of or evaluate the effects of changes in banking company equity valuation from LDC debt exposures. We also perform an event study for three major debt crises to determine whether the market recognizes the effects of these events on bank valuation. The event study results show that there is little information from identifying the time period of the crises on banking company equity returns. Explanations for this are that the information of these possible crises has been embedded in bank changes in exposure and that the market valuation of the emerging market debt is already accounted for by our model.